An Interview with Daniel O'Donnell, Current President of FORCE11. Issue 1 (18th August 2019) - Cook, Eleanor I.; O'Donnell, Daniel Paul
ABSTRACT: An interview was arranged with the current President of FORCE11 in order to discover how this group arose, what its mission and activities are and how and why it might be of interest to readers of Serials Librarian.